(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
The technological developments of the methods of neuroimaging and, in particular, of the new methods of analysis of the dates based on the analysis of functional integration, allow to examine the most complex aspects of brain’s working, by avoiding the risk of a “neofrenology”. The most recent studies deal with aspect of brain’s working that are traditionally considered out of the neurosciences, such as the economic decision, the moral choices and the esthetic experience.